2017
DOI: 10.1016/j.seppur.2017.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal stability of silica, hybrid silica and Zr-doped hybrid silica membranes

Abstract: a b s t r a c tHybrid silica membranes have demonstrated to possess a remarkable hydrothermal stability in pervaporation and gas separation processes allowing them to be used in industrial applications. In several publications the hydrothermal stability of pure silica or that of hybrid silica membranes are investigated. To gain deeper insight into the mechanism of hydrothermal stability of silica-based membranes we report a comparison under identical conditions of the gas permeation performance of silica (TEOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Although the hydrothermal stability of silica membranes has posed a marked limitation in their adoption as a versatile tool for industrial applications, the different solutions in mitigating this feature have spurred several membranes. In one such study conducted by ten Hove et al [ 90 ] silica, hybrid silica as well as zirconium doped silica membranes were analyzed on the basis of gar permeance. The latter two have been derived using 1,2-bis(triethoxysilyl)ethane as a precursor.…”
Section: Applicationsmentioning
confidence: 99%
“…Although the hydrothermal stability of silica membranes has posed a marked limitation in their adoption as a versatile tool for industrial applications, the different solutions in mitigating this feature have spurred several membranes. In one such study conducted by ten Hove et al [ 90 ] silica, hybrid silica as well as zirconium doped silica membranes were analyzed on the basis of gar permeance. The latter two have been derived using 1,2-bis(triethoxysilyl)ethane as a precursor.…”
Section: Applicationsmentioning
confidence: 99%
“…The permselectivity of BTESE-derived silica membranes were almost the same; however, H 2 permeances were largely different from each other. In general, BTESE-derived silica membranes with their intermediate layer of SiO 2 –ZrO 2 showed higher H 2 permeance than those with their intermediate layer of γ-alumina [12,13,14], probably due to the higher permeability of SiO 2 –ZrO 2 intermediate layer than those of γ-alumina intermediate layer. The research group of Hiroshima University used SiO 2 –ZrO 2 intermediate layers and reported high H 2 permeance of BTESE-derived silica membranes [5,15,16]; however, their H 2 permeances differed by one order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…The asymmetric silica membranes are prepared by sol-gel chemistry and the final structure is composed of the following three layers: 1) a macroporous, polished and disc-shaped α-Al2O3 substrate with 2mm thickness, 35% porosity and 80 nm pore size were obtained from Pervatech B.V. the Netherlands; 2) a mesoporous γ-Al2O3 layer with a pore size of 5nm and thickness of 3 µm coated on the α-Al2O3 disc in order to create an intermediate layer working as a bridge to avoid penetration of the relatively small silica particles into the large pores of the α-Al2O3 layer; 3) an amorphous silica top layer with a uniform microstructure having a pore size of much less than 0.5 nm and thickness around 100 nm was coated via sol-gel techniques on the γ-Al2O3 intermediate layer [50,51]. The detailed preparation procedure of these silica multilayer membranes is described in [52].…”
Section: Methodsmentioning
confidence: 99%